Which of5 the following shows the correct process of solving -3^0 + 4.5

-3^0 + 4.5 = - 1.3^0 + 4.5 = - 1.1 + 4.5 =-1+ 4.5 = 3.5

-3^0 + 4.5 = -3^0 + 4.5 = 1 + 4.5 = 1 + 4.5 = 5.5

-3^0 + 4.5 = -3+4.5=1.5

-3^0 + 4.5 = -3.0+4.5=0+4.5=4.4

1 answer

Let's break down the expression -3^0 + 4.5 step by step.

  1. Evaluate \(-3^0\): The expression \( -3^0 \) can be evaluated as follows:

    • Any non-zero number raised to the power of zero is \(1\).
    • So, \( -3^0 = -1 \).
  2. Substituting back into the expression: Now, substitute \( -1 \) back into the expression: \[ -3^0 + 4.5 = -1 + 4.5 \]

  3. Calculating the result: \[ -1 + 4.5 = 3.5 \]

So, the correct process to solve the expression is:

  • The correct answer is \( -3^0 + 4.5 = -1 + 4.5 = 3.5 \).

Now, let's evaluate the options provided:

  1. Option 1: Incorrect. The steps contain errors.
  2. Option 2: Incorrect. The evaluation of \( -3^0 \) is miscalculated.
  3. Option 3: Incorrect. The evaluation does not follow the correct exponent rule.
  4. Option 4: Incorrect. Misapplies rules and calculations.

None of the options correctly show the steps. The right calculation is \( -1 + 4.5 = 3.5 \).